Generating intuitive behaviour in artificial intelligence - Waseem, Chaudhry Talha; Hameed, Dr. Vazeerudeen Abdul; Ramachandiran, Chandra Reka (Journal of Applied Technology and Innovation, 2021)
Intuition is a sub-conscious but highly effective decision-making process that makes us questions and increase our intelligence. It is generated on the emotional/creative side of our brain and is something that have been proven to be nonexistent for machines. A stimulation is also presented in this study that will help develop an algorithm that mimic the human intuition process. The main question focused in this study is that can a machine become able to figure out the unknown. This study concludes with the potential areas of where this algorithm can be implemented or what would be the ideal application that can use the intuitive artificial intelligence to answer the unknown.